An evaluation of rural policies and approaches in Türkiye in the planned period within the scope of quality of life - Yoruten, Gunes; Hamamcioglu, Cenk (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2025)
Rural policies and approaches shape the physical, economic, social, and environmental dimensions of rural life. When well-designed and implemented, they lead to improved living standards, greater opportunities, and sustainable development, all of which are core components of quality of life. Since the founding of the Republic, T & uuml;rkiye has developed numerous policies and approaches to address rural settlements. However, comparative analyses examining these policies and their impact on the quality of life in rural areas remain scarce in the existing literature. In this regard, this study investigates T & uuml;rkiye's rural settlement policies and approaches during the Planned Period (1963-present) through the lens of quality of life. It does so by assessing the extent to which these policies incorporate quality of life aspects, identifying areas that have been addressed and those that have been neglected, and offering insights for future policy development. To this end, the study conducts a comprehensive review of relevant literature and policy documents, offers a comparative evaluation of rural policies in the context of quality of life, and discusses the findings to support the formulation of future approaches. The key recommendations of this research include: (1) clearly defining the tools and mechanisms for implementing policy strategies; (2) increasing the state's role in developing new approaches and applications for rural settlements; (3) addressing each settlement's unique priorities for sustainable development; and (4) holistically evaluating the multiple dimensions comprising rural quality of life.
Keywords: Article history; Rural development policies in; T & uuml; rkiye; rural planning; rural; Architecture